2020
DOI: 10.3390/antiox9121228
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Viral Potential and Modulation of Nrf2 by Curcumin: Pharmacological Implications

Abstract: Nuclear factor erythroid 2-related factor 2 (Nrf2) is an essential transcription factor that maintains the cell’s redox balance state and reduces inflammation in different adverse stresses. Under the oxidative stress, Nrf2 is separated from Kelch-like ECH-associated protein 1 (Keap1), which is a key sensor of oxidative stress, translocated to the nucleus, interacts with the antioxidant response element (ARE) in the target gene, and then activates the transcriptional pathway to ameliorate the cellular redox con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 174 publications
0
43
0
2
Order By: Relevance
“…In addition to the nutraceuticals analyzed, the role of other nutraceuticals has been explored. Curcumin is a yellow polyphenolic curcuminoid from Curcuma longa (turmeric) that seems to have a broad spectrum of bioactivities, including antioxidant, antiapoptotic, and antifibrotic properties with inhibitory effects on Toll-like receptors, NF-κB, inflammatory cytokines and chemokines, and bradykinin [ 235 , 236 ]. Interestingly, Curcumin can be appraised to hinder cellular entry and replication of SARS-CoV-2 and to prevent and repair COVID-19-associated damage of pneumocytes, renal cells, cardiomyocytes, and hematopoietic stem cells [ 237 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the nutraceuticals analyzed, the role of other nutraceuticals has been explored. Curcumin is a yellow polyphenolic curcuminoid from Curcuma longa (turmeric) that seems to have a broad spectrum of bioactivities, including antioxidant, antiapoptotic, and antifibrotic properties with inhibitory effects on Toll-like receptors, NF-κB, inflammatory cytokines and chemokines, and bradykinin [ 235 , 236 ]. Interestingly, Curcumin can be appraised to hinder cellular entry and replication of SARS-CoV-2 and to prevent and repair COVID-19-associated damage of pneumocytes, renal cells, cardiomyocytes, and hematopoietic stem cells [ 237 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a natural compound, curcumin has been reported to have antiviral activity against various viruses, including the novel SARS-CoV-2 [ 28 , 29 ]. Our research confirmed that curcumin could inhibit HPIV3 infection, and its antiviral effect is dose-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds, such as curcumin and resveratrol, are potential NRF2 modulators in cancer prevention and therapy [ 72 ], and their chemopreventive properties can be enhanced by encapsulation in nanoemulsions. Curcumin, (1E,6E)-1,7-bis(4-hydroxy-3-methoxyphenyl)hepta-1,6-diene-3,5-dione, is a natural hydrophobic polyphenol that presents in the dried rhizomes of the medicinal plant Curcuma longa (turmeric), and its biological and pharmacological activities have been widely reported [ 119 , 120 ].…”
Section: Nddss In the Delivery Of Nrf2 Modulators For Cancer Therapymentioning
confidence: 99%
“…Several studies demonstrated the ability of curcumin to reactivate the expression of antioxidant enzymes, such as glutathione S-transferase, aldose reductase, and HO-1, through KEAP1/NRF2 signaling [ 119 ]. Curcumin could be a possible NRF2 activator to regulate the cell signaling pathway in stress environments and be beneficial in treating several oxidative stress-related disorders, such as cancer (including breast, gastrointestinal, and prostate), neurodegenerative diseases (NDs), autoimmune diseases, and cardiovascular diseases (CVDs), among others [ 119 , 120 ].…”
Section: Nddss In the Delivery Of Nrf2 Modulators For Cancer Therapymentioning
confidence: 99%